Comparisons of surface and optical properties of the heavily carbon-doped GaN nanocrystalline films deposited by thermionic vacuum arc method. (November 2016) - Pat, Suat; Özen, Soner; Şenay, Volkan; Korkmaz, Şadan
Abstract: In this paper, heavily C-doped GaN samples were deposited on glass and PET substrates by the thermionic vacuum arc (TVA) method, for the first time. Microstructure, surface and optical properties of the carbon-doped GaN samples were investigated by X-ray diffraction (XRD), field emission scanning electron microscopy, atomic force microscopy, and UV–Vis spectrophotometer. According to XRD pattern, fullerene (C60 ) structures were able to deposit in doped samples, for the first time. The fullerene structures were detected at heavily carbon-doped GaN. The obtained band gap changes of heavily carbon-doped GaN samples are determined. The band gap of CGaN on PET substrate decreased to a lower value, about 100 meV. The band gaps were shifted to the lowest wavelengths towards the edge of the UV region by heavily doped carbon. (002) and (004) peaks for GaN were also detected. Highlights: Fullerenes were doped to GaN material. Optical properties of the fullerenes doped GaN were determined. Surface properties of the fullerenes doped GaN were determined.